2015
DOI: 10.1016/j.jconrel.2015.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumor activity of camptothecin–doxorubicin combinations and their conjugates with hyaluronic acid

Abstract: Combinations of topoisomerase inhibitors I and II have been found to synergistically inhibit cancer cell growth in vitro, yet clinical studies of these types of combinations have not progressed beyond phase II trials. The results of clinical combinations of topoisomerase (top) I and II inhibitors typically fall within one of two categories: little to no improvement in therapeutic efficacy, or augmented toxicity compared to the single drug counterparts. Hence, despite the promising activity of top I and II inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 61 publications
3
75
1
Order By: Relevance
“…The concentrations required to inhibit 50% cell growth (D 50 ) of DOX-PVA and CPT-PVA were 1.5 μM DOX and 14 μM CPT, respectively. In comparison, previous studies in our lab demonstrated D 50 concentrations of free DOX and CPT to be 0.3 μM and 100 μM, respectively [20]; hence, conjugation to 10 kDa PVA reduced activity of DOX, whereas it enhanced activity of CPT. The enhanced anticancer activity of PVA-bound CPT may be attributed to its enhanced water solubility upon conjugation to PVA.…”
Section: Resultscontrasting
confidence: 66%
See 4 more Smart Citations
“…The concentrations required to inhibit 50% cell growth (D 50 ) of DOX-PVA and CPT-PVA were 1.5 μM DOX and 14 μM CPT, respectively. In comparison, previous studies in our lab demonstrated D 50 concentrations of free DOX and CPT to be 0.3 μM and 100 μM, respectively [20]; hence, conjugation to 10 kDa PVA reduced activity of DOX, whereas it enhanced activity of CPT. The enhanced anticancer activity of PVA-bound CPT may be attributed to its enhanced water solubility upon conjugation to PVA.…”
Section: Resultscontrasting
confidence: 66%
“…Conjugation of chemotherapy drugs to polymers typically alters drug activity, as was evident in our previous study of 250 kDa hyaluronic acid conjugated to CPT and DOX [20]. However, drug activity should not be compromised so much as to entirely prevent its anticancer effects.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations